Impact of lifestyle on erectile dysfunction: literature review and educational recommendations - Wawszkowicz, Konrad; Dyląg, Liliana; Graca, Magdalena; Szopińska, Kinga; Łowicka, Weronika; Szeliga, Anna; Szostak, Agata; Korta, Karolina; Oluszczak, Karolina; Śmigielska-Mikołajczyk, Maria Janina (Quality in Sport, 2024)
Introduction: Erectile dysfunction (ED) represents a significant health problem that can have a negative impact on men's quality of life, intimate relationships and self-esteem. ED is a marker of overall health, requiring a comprehensive diagnostic and therapeutic approach. This article highlights the need for an integrated approach, in which lifestyle modifications are key to the successful treatment of erectile dysfunction. Aim of the study: The aim of this article is to provide a comprehensive review of the literature on erectile dysfunction, with the intention of improving understanding of the condition and providing directions for future research and clinical practice. Materials and methods: Electronic databases, including PubMed, Scopus, Web of Science, and Google Scholar, were searched to identify studies and literature reviews on erectile dysfunction (ED). The state of knowledge: This review examines the epidemiology, pathophysiology, and risk factors associated with ED, emphasizing the importance of lifestyle in prevention and treatment. The role of diet, physical activity, weight reduction, smoking cessation, and alcohol restriction in improving erectile function is discussed. The article also presents current diagnostic and therapeutic approaches, including pharmacotherapy, alternative therapies and psychological interventions. Conclusions: Erectile dysfunction (ED) is a complex health issue that necessitates a comprehensive and interdisciplinary diagnostic and therapeutic approach. Lifestyle plays a pivotal role in the prevention and treatment of ED, and its modification should be an integral component of any treatment plan.